Development of the Family Education Activities Evaluation Scale - Serçe, Sinem; Ünver, Naim (Kastamonu Egitim Dergisi, 2025)
Purpose: This study aimed to revise the “Evaluation Scale of OBADER Family Education Sessions Delivered via Distance Education,” developed within a thesis, into a more general scale titled the “Family Education Activities Evaluation Scale.” Design/Methodology/Approach: The study employed the survey model, a quantitative research method, and was conducted in two phases. In the first phase, the original version of the scale was developed based on data collected from 310 participants. In the second phase, carried out two years later, the revised version of the scale was administered to a new sample of 241 participants. Findings: In both phases, the scale consisted of 16 items grouped under 3 factors. While the item contents were slightly modified during the revision process, the overall factor structure was preserved. The results confirmed the scale's validity and reliability across both samples. Highlights: The final version of the scale, titled “Family Education Activities Evaluation Scale,” provides a valid and reliable tool for evaluating various family education activities beyond the initial OBADER context, making it adaptable for broader applications in distance education and family training programs.